Case Report: Craniofacial deafness hand syndrome with unusual cardiovascular symptoms and lack of holistic care - Saenz Hinojosa, Samantha; Reyes-Silva, Carlos; Hosomichi, Kazuyoshi; Romero, Vanessa I. (Frontiers in Genetics, 2025)
BackgroundDelays in diagnosing rare genetic disorders often arise due to limited awareness and systemic challenges in primary care. This case highlights the importance of a holistic approach to patient care, encompassing timely detection and comprehensive evaluation of clinical features.MethodsWe report the case of a 21-year-old Ecuadorian male with facial and hand dysmorphias, cardiomegaly, pulmonary hypertension, and patent ductus arteriosus (PDA). Whole-exome sequencing, performed using the Illumina NextSeq platform. We extensively analyzed over 100 genes linked to congenital structural heart diseases.ResultsThe genetic findings provided a definitive diagnosis of Craniofacial-Deafness-Hand Syndrome, an extremely rare autosomal dominant condition, but found no variants that explain the patient’s cardiac phenotype. We identified a novel pathogenic missense variant in the PAX3 gene (c.A91C, p. T31P).Discussion and conclusionsThis case underscores the necessity of integrating genetic testing into routine clinical practice to enhance diagnostic precision for rare diseases. It also highlights the need for multidisciplinary collaboration and a holistic care model to improve patient outcomes. The unique association of Craniofacial-Deafness-Hand Syndrome with cardiovascular anomalies due to a PAX3 variation provides valuable insights into the genetic underpinnings of this rare condition.